Role of halides in selective oxidation reactions - Burch, R; Squire, G; Tsang, S (1990)
The role of chlorine, in various chemical forms, in the methane activation reaction has been investigated. It has been found that although there is a release of methyl chloride and HCl from the surface of chloride-containing catalysts during the methane coupling reaction, very little ethene is produced from ethane in the post catalyst volume. However, depending on the experimental conditions used, it is possible to envisage an important contribution from gas phase reactions in the catalyst bed.